Mathematical Problem-Solving on Slow Learners Based on Their Mathematical Resilience - Ayu Faradillah; Yasmin Husna Restu Fadhilah (Jurnal Elemen, 2021)
This study aims to describe mathematical resilience on slow learner students in solving problems. According to the previous research, there is no research focused on the subject of slow learners. The research method is a qualitative descriptive approach. The total population of this study was 71 students with special needs, which consisted of 51 male students and 20 female students. The selection of subjects in this study was reviewed based on three levels of mathematical resilience, namely high, medium, and low. The process of selecting this subject uses the Wright Maps table on Winsteps application version 3.73. Selected subjects were given instruments and interviews to analyze their mathematical problem-solving. The results showed that mathematical resilience on slow learner students was directly proportional to solving mathematical problems for subjects with high mathematical resilience. Meanwhile, subjects with medium and low mathematical resilience were inversely proportional to solving mathematical problems. The stages of solving the problem of the slow learners were incomplete because they have not passed one of the stages formulated by Polya. Therefore, based on the results of this research analysis, teachers can pay more attention to the slow-learners learning strategies in solving problems.